INTELLECTUAL EDUCATION OF STUDENTS OF PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS BY MEANS OF FOREIGN LANGUAGE IN EXTRACURRICULAR WORK - Petʹko Л. В. (Pedagogy of Higher and Secondary Education, 2022)
Actual aspects of the problem of the intellectual education of the students of the higher school as future teachers are considered in this article.